Looking for loopholes : processes of incorporation of illegal immigrants in the Netherlands - Leun, Joanne van der (Amsterdam University Press, 2003)
"Looking for Loopholes, Processes of incorporation of illegal immigrants in the Netherlands offers a detailed account of how illegal immigrants, who are legally excluded, manage to incorporate into Dutch society. By combining the perspectives of immigrants on the one hand and of those who have to implement the 'discouragement policy' on the other hand, the study shows how tensions between restrictive rules and day-to-day practices are growing. Based on long-term research in the four largest cities in the Netherlands, attention is paid to the role of informal employment and criminal involvement and to practices in the fields of education, housing, health-care and police surveillance"--Publisher's description